Socialization of Orphans. Features and Assessment Methods - Bolman, S.; Shkuropat, K. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
The article deals with violations of the process of socialization of orphans. The authors reveal design features, validity and adaptation of developed by them questionnaire, which is designed to diagnose the level of socialization of orphans.